Density Functional Theory Simulation of Iron-Montmorillonite as Carbon Dioxide Adsorber - Ihsudha, Husni; Wungu, Triati Dewi Kencana; suprijadi, suprijadi; Morikawa, Yoshitada (Institut Teknologi Bandung, 2023)
Carbon dioxide (CO2) is a greenhouse gas that naturally keep the Earth^s surface temperature warm but currently the levels cause environmental problem such as climate change. Carbon capture and storage (CCS) technology is built to reduce CO2 gas emissions by binding carbon dioxide molecules and then storing them or utilising them as more useful products. In this study, simulations were carried out for the addition of iron (Fe) impurities as additional cation in montmorillonite to see the increase in the ability to bind carbon gas. Density Functional Theory calculations were carried out using additional corrections such as Van der Waals (vdW) and Hubbard-U. Here we got that Fe cation can help CO2 adsorbtion compare with other site without Fe atom by adding acid cite condition. But to adsorb CO2, the structure need initial process to swell the montmorillonite interlayer to certain optimum distance.